Thyroiditis- A Challenging Case Report that Used PET-CT for Definitive Diagnosis in a Non-COVID Patient During COVID-19 Pandemicc - Sethuraman, Raghuraman M; Venkatraman, Indiran; P, Shanthi (Journal of Medicine, 2023)
A whole-body PET scan coupled with contrast-enhanced CT was performed on a 45-year-old woman with persistent fever for 3 weeks. This was performed to make a definitive diagnosis in a few hours as an out-patient itself to avoid admission / frequent visits to the hospital during the COVID-19 pandemic for this non-COVID patient. Although step-wise investigations such as ultrasound, thyroid antibodies, and biopsy would be ideal and devoid of radiation, other co-existing causes for fever if any (malignancy, other non-infectious causes) might have been missed. Therefore, in addition to confirming the clinical diagnosis (Thyroiditis), whole-body PET-CT helped to rule out other causes of fever of 3-week duration. Therefore, we wish to highlight the unique approach that we adopted here due to the restrictions on admissions during the pandemic for this non-COVID patient. J MEDICINE 2023; 24(2): 152-154